Measuring satisfaction of engineering technology students in Malaysian public universities - Ali, Rosmah; Hussain, Noor Hamizah; Mohd Ismail, Kamsiah; Radin Salim, Kamilah; Haron, Habibah@ Norehan; Mohamed Noor, Norhayati; Abdullah, Morina; Mohamed, Zainai; Mulop, Normah; Abd Rahman, Rozita Juliana (American Scientific Publishers, 2016)
This paper reports the results of a study on Engineering Technology student satisfaction at Malaysian public universities. Engineering Technology undergraduate programs are relatively new in Malaysia. The programs aim to produce highly-skilled human resources to meet the industry requirements. The level of student satisfaction will affect future student enrollment in the programs, and thus will subsequently affect the quantity and quality of future graduates. It is, therefore important to measure student satisfaction with their experience in the programs to support institutional strategic planning and decision making to improve the programs. A survey questionnaire was designed and administered to 491 students from three public universities offering engineering technology programs in Malaysia. Survey items were subdivided into three main groups, namely teaching and learning experience, facilities provided, and the programs as a whole. Statistical analysis was conducted using PASW Statistics. Findings show that students were highly satisfied with their learning experience, the facilities provided, and the overall programs.